2007
DOI: 10.1111/j.1399-3046.2007.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complaints and lung function after pediatric kidney transplantation

Abstract: Recently four of 38 children with a kidney transplant were diagnosed with bronchiectasis. The aim of the current study was to identify patients with increased risk for pulmonary damage. In this cross-sectional observational study, children with a functioning kidney graft in the Netherlands and Antwerp, Belgium, were screened with the use of a symptom checklist and spirometry. Maximum score for upper airway complaints was 21 (normal: <8), for lower airway complaints 28 (<10). Results of FVC, FEV(1) and MEF(25) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…We chose not to include non-vagotomized animals in these studies because human lungs are denervated following transplantation and denervated mice chronically treated with immunosuppressive drugs seemed the best model for translating our findings to humans, which is our goal. Our findings do not rule out the possibility that treatment with immunosuppressive drugs could affect MCC in non-denervated animals and in humans who have not undergone lung transplantation [18] [19] . For this reason, a group of non-vagotomized mice would be interesting to look at in future studies in order to determine the potential impact of chronic immunosuppression on MCC in transplant populations that don’t undergo denervation (i.e.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We chose not to include non-vagotomized animals in these studies because human lungs are denervated following transplantation and denervated mice chronically treated with immunosuppressive drugs seemed the best model for translating our findings to humans, which is our goal. Our findings do not rule out the possibility that treatment with immunosuppressive drugs could affect MCC in non-denervated animals and in humans who have not undergone lung transplantation [18] [19] . For this reason, a group of non-vagotomized mice would be interesting to look at in future studies in order to determine the potential impact of chronic immunosuppression on MCC in transplant populations that don’t undergo denervation (i.e.…”
Section: Discussioncontrasting
confidence: 87%
“…Our findings do not rule out the possibility that treatment with immunosuppressive drugs could affect MCC in non-denervated animals and in humans who have not undergone lung transplantation [18][19]. For this reason, a group of non-vagotomized mice would be interesting to look at in future studies in order to determine the potential impact of chronic immunosuppression on MCC in transplant populations that don’t undergo denervation (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…Another proposed mechanism is direct damage to the airway wall and this is discussed in a number of studies, including the Netherlands group who hypothesised that MMF might influence ciliary motility. They also reported resolution of respiratory symptoms in the four paediatric cases after withdrawal of MMF 5,6,9 . A clear pathological process for a direct mechanism of action on respiratory function has not yet been determined to our knowledge.…”
Section: Discussionmentioning
confidence: 96%
“…Over a decade ago, adult and paediatric kidney transplant groups from the Netherlands reported small case series of kidney transplant recipients developing bronchiectasis, both citing it as a newly emerging phenomenon 5,6 . Subsequently, seven adult cases were reported from the UK and a multicentre study across 14 French transplanting units reported 46 adult cases in 2015 7,8 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 1 more Smart Citation